UTILIZATION OF BIG DATA ON ELECTION POLITICS INDONESIA IN INDUSTRY 4.0 - Elyta, Elyta; Olifiani, Laras Putri; Afhiani, Syarifah Nurma; Usmulyadi, Syarif (Universitas Padjadjaran, 2023)
The development of technology, information, and communication has entered all aspects of life, including politics, through big data technology. In electoral politics, the quick count method is considered superior to the manual process. However, the level of accuracy depends on industry 4.0. This study analyzed the potential for using big data in electoral politics. This research uses a descriptive method with a qualitative approach. Data obtained through literature study. Data analysis is done by collecting data, making an analysis, and concluding. This study found that big data is the right technology to facilitate electoral politics in Indonesia. The results of the significant data method have complemented and validated the old way.